What is the welfare sub-regime of Medellin-Colombia? (2021)
This research recognizes the weaknesses of the analysis of welfare regimes based on national taxonomies and proposes a "local variation", arguing the benefits of delimiting national territories due to their regional differences and different local needs. In this sense, we analyze which are the ways to produce welfare in Medellín between the years 2016-2019, whose findings show that state agencies assume that social risks are an exclusive condition of some population groups. And, in the face of an unequal incorporation of marginalized groups and a high commodification of welfare, a large part of social risk management falls exclusively on the family and on women's unpaid work. This article begins with a review of the existing literature in Latin America on welfare regimes, continuing with the elaboration of some analysis criteria that will allow grouping the welfare sub-regime of the city within one of the typifications used for this research. Finally, the findings of the empirical analysis and conclusions are presented.